Superior mesenteric artery syndrome as a cause for recurrent abdominal pain and vomiting in a 9-year-old girl. (26th February 2015) - Forsyth, James Michael; Muhammad, Karim; Mahmood, Khalid
Abstract : A 9-year-old girl was admitted under our general surgical team with 2 days of diffuse abdominal pain and vomiting. This was one of multiple admissions for similar symptoms over the past 5 years. She was feverish on admission but haemodynamically stable. On examination, she had a diffusely tender and hypersensitive abdomen, with no guarding or peritonism, and no palpable masses. Of note, the patient was very thin, with almost no body fat. Blood tests were otherwise normal, with a normal abdominal X-ray and abdominal ultrasound. She had undergone three previous abdominal ultrasounds over the past 5 years for similar symptoms, all of which were normal. Following this, CT revealed a diagnosis of superior mesenteric artery syndrome. The patient was transferred to our regional children's hospital for analgaesia, nasogastric decompression and nutritional supplementation. She made a swift improvement with plans for ongoing follow-up by the paediatric team.